Otelo e Circuito Iago: Metáforas no processo de transcriação da tragédia em dança - Barcellos, Fernando Borges (2023)
In this thesis in five acts, an autoethnography (FORTIN, 2009), I analysed the creation process of my own solo dance performance Circuito Iago (Iago’s Circuit) as an intersemiotic translation of Othello, a tragedy by William Shakespeare. Such translation was investigated as a transcreation, concept by Haroldo de Campos (2015, 2006). In order to contribute to this approach, I used the notion of translation as manipulation according to Aslanov (2015). Based on the principle that, in the transcreation process, the transcreator’s choices – in this thesis understood as a Machiavellian choreographer – are always revealing, I analysed my choices in the process mentioned. This analysis conducted to the notions of Apollonian images and Dionysian pathologies, shaped after the conceptions of the tragic by, among others, Nietzsche (2013), Szondi (2004) and Lesky (2003). One of the hypotheses of this work is that the choreographic strategies that I use in my transcreation processes can be studied as metaphors, which are, in turn, composed by images and pathologies. The dramaturgy of Circuito Iago would be, thus, constituted of metaphors whose meanings may vary depending on the experience of the spectator. In order to weave the notions that I used in this thesis, I recurred to, besides the references already cited, the discussions of thinkers from contemporary dance (LEPECKI, 2017, 2016a, 2016b; LOUPPE, 2012; ROCHA, 2016), metaphor (RICŒUR, 2005, 2003, 1978; LAKOFF & JOHNSON, 2003, 1999), philosophy (DERRIDA, 2014, 1992, 1988; BLANCHOT, 2010, 2005; AGAMBEN, 2009; DELEUZE, 1997), and Shakespearean studies (JACOBSEN, 2009; NEILL, 2008; KOTT, 2003; MOISAN, 2002).